Evolution of the “Production-Living-Ecological” space of urban trituration and its prediction of carbon mitigation potential–The case of Xi’an - Jinzhao Song; Jie Lei; Peijia Wang (Ecological Indicators)
Under the perspective of spatial low-carbon optimization, revealing the changes in the production-living-ecological space pattern and its carbon emission pattern of the historical capital-type city is of great significance for deepening the theory of land use transformation and helping the country achieve its dual-carbon goal. Therefore, spatial transfer matrix and dynamic analysis are used to study the transformation characteristics of space in Xi’an from 2000 to 2020, and the spatial and temporal evolution pattern of carbon emissions in the region and the impact of spatial transformation on carbon emissions are identified and simulated by the carbon emission accounting method and the patch-generating land use simulation (PLUS) model. The results show that the spatial of Xi’an City during the study period is characterized by a pattern of high in the south and low in the north, and the trend of spatial transition is characterized by slow fluctuation in the early stage and dramatic development in the late stage. The net carbon emission of Xi’an City showed a fluctuating increase, and the net carbon emission increased by 3,683,800 tons in 20 years. The mutual transformation between rural production space, grassland ecological space and urban production space mainly leads to the increase or decrease of carbon emissions. The drivers of spatial expansion are mainly elevation, annual precipitation and GDP density. The relatively low net carbon emissions of the 2030 spatial utilization of Xi’an under the social priority development scenario can provide a reference for the future territorial planning of Xi’an.